2014
DOI: 10.1242/dev.101808
|View full text |Cite
|
Sign up to set email alerts
|

Molecular identification of venous progenitors in the dorsal aorta reveals an aortic origin for the cardinal vein in mammals

Abstract: Coordinated arterial-venous differentiation is crucial for vascular development and function. The origin of the cardinal vein (CV) in mammals is unknown, while conflicting theories have been reported in chick and zebrafish. Here, we provide the first molecular characterization of endothelial cells (ECs) expressing venous molecular markers, or venous-fated ECs, within the emergent dorsal aorta (DA). These ECs, expressing the venous molecular markers Coup-TFII and EphB4, cohabited the early DA with ECs expressin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
55
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(65 citation statements)
references
References 33 publications
7
55
0
Order By: Relevance
“…Later on, a subpopulation of venous-fated angioblasts in the DA sprouts ventrally to give rise to the PCV (Herbert et al, 2009;Jin et al, 2005). Most recently, a study conducted in mice demonstrated that at least ∼15% of the CV cells originate in the DA (Lindskog et al, 2014; reviewed by Potente et al, 2011). In line with the findings of Herbert et al (2009), this work demonstrated that the DA harbors a heterogeneous population of venous and arterial ECs early during vasculogenesis, with the venous ECs being those that generate the CV (Lindskog et al, 2014).…”
Section: The Origin Of Organ-specific Lymphatic Vesselssupporting
confidence: 70%
“…Later on, a subpopulation of venous-fated angioblasts in the DA sprouts ventrally to give rise to the PCV (Herbert et al, 2009;Jin et al, 2005). Most recently, a study conducted in mice demonstrated that at least ∼15% of the CV cells originate in the DA (Lindskog et al, 2014; reviewed by Potente et al, 2011). In line with the findings of Herbert et al (2009), this work demonstrated that the DA harbors a heterogeneous population of venous and arterial ECs early during vasculogenesis, with the venous ECs being those that generate the CV (Lindskog et al, 2014).…”
Section: The Origin Of Organ-specific Lymphatic Vesselssupporting
confidence: 70%
“…The Notch receptors are transmembrane proteins that promote arterial endothelial cell (EC) specification by enhancing expression of arterial molecular markers and suppressing the expression of venous markers (12)(13)(14)(15)(16)(17)(18)(19). Abnormal signaling induces enlarged AV connections and shunting in mouse and zebrafish embryos (12)(13)(14).…”
mentioning
confidence: 99%
“…Abnormal signaling induces enlarged AV connections and shunting in mouse and zebrafish embryos (12)(13)(14). Notch activity is aberrantly increased in the endothelium of human brain AVMs (18,20), suggesting that it may participate in the growth or maintenance of human AVMs.…”
mentioning
confidence: 99%
“…The modelling of two major vessels, the dorsal aorta and the cardinal vein, during embryonic development requires repulsive signalling between ephrin-B2 and EphB4 in endothelial cells (ECs) [101,102]. Initially shown in zebrafish [103], and then in mouse [104], the dorsal aorta forms first and harbours a mixed population of venous (EphB4+) and arterial progenitors (ephrin-B2+). Both studies have shown that the formation of the cardinal vein is regulated by repulsive signalling between EphB4 and ephrin-B2.…”
Section: Ephb4 and Ephrin-b2 Function In Normal Human Developmentmentioning
confidence: 99%
“…Signalling between both EphB4 and ephrin-B2 repels venous ECs from arterial ECs generating an EphB4+ cardinal vein [103,104]. During the early stages of embryo development lymphatic ECs differentiate from the cardinal vein and other venous derivatives [105].…”
Section: Ephb4 and Ephrin-b2 Function In Normal Human Developmentmentioning
confidence: 99%